Phase 2 study of everolimus for relapsed or refractory classical Hodgkin lymphoma - Patrick B. Johnston; Lauren C. Pinter-Brown; Ghulam Warsi; Kristen White; Radhakrishnan Ramchandren (Experimental Hematology & Oncology, 2018)
Abstract Background The current standard of care for classical Hodgkin lymphoma (HL) is multiagent chemotherapy with or without radiation. In patients who relapse or fail to respond, additional high-dose chemotherapy with autologous hematopoietic stem cell transplantation (AHSCT) can improve progression-free survival (PFS). Novel therapies are required for patients refractory to chemotherapy and AHSCT. The mammalian target of rapamycin inhibitor everolimus has shown preliminary activity in preclinical models of HL and promising efficacy in patients with relapsed or refractory HL. Methods This was an open-label, two-stage, phase 2 study that enrolled 57 patients aged ≥ 18 years with classic HL that had progressed after standard therapy. Patients received everolimus 10 mg daily until disease progression, intolerable toxicity, withdrawal of consent, or investigator decision. The primary endpoint was overall response rate; secondary endpoints included PFS, overall survival, time to response, duration of response, and safety. Results Overall response rate was 45.6% (95% confidence interval [CI] 32.4–59.3%); five patients (8.8%) experienced a complete response and 21 patients had a partial response (36.8%). Median PFS was 8.0 months (95% CI 5.1–11.0 months). Seven patients (12%) were long-term responders (≥ 12 months). The most common study drug-related adverse events were thrombocytopenia (45.6%), fatigue (31.6%), anemia (26.3%), rash (24.6%), and stomatitis (22.8%). Conclusions Everolimus 10 mg/day demonstrated favorable results in patients with heavily pretreated, relapsed, or refractory classical HL. These findings support the further evaluation of everolimus in this indication. Trial registration ClinicalTrials.gov NCT01022996. Registered November 25, 2009